Evaluating the Reproducibility of Amplicon Sequencing Data Derived from Deep-Sea Cold Seep Sediment-Associated Microbiota - Jie Kong; Jingchun Feng; Liwei Sun; Si Zhang (Microbiology Spectrum, 2023)
ABSTRACT Benefiting from the rapid developments and wide applications of high-throughput sequencing, great advancements have been made in investigating microbiota, which are highly diverse and play key roles in both element cycling and the energy flow of ecosystems. There have been inherent limitations of amplicon sequencing that could introduce uncertainty and raise concerns about the accuracy and reproducibility of this technology. However, studies focusing on the reproducibility of amplicon sequencing are limited, especially in characterizing microbial communities in deep-sea sediments. To evaluate reproducibility, 118 deep-sea sediment samples were used for 16S rRNA gene sequencing in technical replicates (repeated measurements of the same sample) that demonstrate the variability of amplicon sequencing. The average occurrence-based overlaps were 35.98% and 27.02% between two and among three technical replicates, respectively, whereas their abundance-based overlaps reached 84.88% and 83.16%, respectively. Although variations of alpha and beta diversity indices were found between/among technical replicates, alpha diversity indices were similar across samples, and the average beta diversity indices were much smaller for technical replicates than among samples. Moreover, clustering methods (i.e., operational taxonomic units [OTUs] and amplicon sequence variants [ASVs]) were shown to have little impact on the alpha and beta diversity patterns of microbial communities. Taken together, although there are variations between/among technical replicates, amplicon sequencing is still a powerful tool with which to reveal diversity patterns of microbiota in deep-sea sediments. IMPORTANCE The reproducibility of amplicon sequencing is vital for whether the diversities of microbial communities could be accurately estimated. Thus, reproducibility influences the drawing of sound ecological conclusions. Nevertheless, few studies have focused on the reproducibility of microbial communities that are characterized by amplicon sequencing, and studies focusing on microbiota in deep-sea sediments have been especially lacking. In this study, we evaluated the reproducibility of amplicon sequencing targeting microbiota in deep-sea sediments of cold seep. Our results revealed that there were variations between/among technical replicates and that amplicon sequencing was still a powerful tool with which to characterize the diversities of microbial communities in deep-sea sediments. This study provides valuable guidelines for the reproducibility evaluation of future work in experimental design and interpretation.